Bilateral Neck of Femur Fractures in a Bilateral Below-Knee Amputee: A Unique Case. (6th January 2016) - Lancer, Hannah R.; Smitham, Peter; Ray, Pinak
Abstract : According to the National Hip Fracture Database, over 64, 000 patients were admitted with a hip fracture across England, Wales, and Northern Ireland in 2013, but very few are bilateral, and there are no current cases in the literature of bilateral neck of femur fractures in a patient with bilateral below-knee amputations. We present a case of a 69-year-old bilateral below-knee amputee male admitted to the emergency department with bilateral hip pain and radiological evidence of bilateral displaced neck of femur fractures. The patient subsequently underwent synchronous bilateral total hip replacements under general anaesthetic and an epidural and then went on to make a full recovery. He was discharged 27 days after arrival in hospital. Outpatient follow-up at 3 months has shown that the patient has returned to a similar level of preinjury function and is still able to carry out his daily activities with walking aids and bilateral leg prostheses.